Pengaruh Physical Enveronment Dan Kepercayaan Terhadap Komitmen Nasabah Bank Nagari Cabang Sijunjung (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2019)
This study aims to see the effect of the influence Phisycal Enveronment and trust on customer commitment at Bank Nagari Sijunjung Branch. The sample in this study were customers at Bank Nagari Sijunjung Branch in Sijunjung as many as 100 research samples. This study used incidental sampling as the sampling technique. The results of the t-test statistics used to draw conclusions in this study is where phisycal environment has positive and significant effect on customer commitment. For the trust variable have a positive and significant effect on customer commitmnet. F statistic test results where the variables of phisycal enveronment and trust together influence the customer commitment at bank Nagari Sijunjung Branch. The results of determination test magnitude of the influence of the independent variable on the dependent variable is 68,7%.